Talleres creativos del foamy dirigido a las maestras de primer año de preparatoria de educación básica de la provincia de Cotopaxi del cantón Latacunga del sistema fiscal en el sector urbano en el periodo 2012-2013 - Llumiquinga Chancusig, Johana Elizabeth (2013)
The implementation of creative workshops of foamy play a leading role in the current and future development of both the master assistants as well as children of the first year of basic education with the aim of achieving analytical, participatory, entities with a good drive and very creative development through a good stimulation to the time to develop didactic material for the teaching of classes that are part of a broad knowledge to cope in the journal live.